The Influence of Film Tourism on Interest in Visiting Lake Toba Tourist Destinations Mediated by Motivation: (Case Study of the Movie "Ngeri-Ngeri Sedap") - Limbong, Elesabet Octaria; Erida, Erida; Wulan, Sylvia Kartika (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to determine the effect of the Ngeri-Ngeri Sedap film on interest in visiting Lake Toba tourist destinations mediated by motivation (case study film "Ngeri-Ngeri Sedap "). This study employs quantitative approaches and data collection techniques, including the distribution of Likert scale questionnaires. The population in this study was 2,886,121 people with a sample using the 10% percentage Sovin formula with a total of 100 respondents. By using SmartPLS 4.0 software, data testing techniques use the R-Square Test, Validity Test, Reliability Test and Hypothesis Test using Bootstrapping. The results of this study indicate that the destination image in the movie Ngeri-Ngeri Sedap has a significant effect on interest in visiting Lake Toba tourist destinations in mediation Motivation.